USAHATANI KAKAO DALAM PERSPEKTIF PENDAPATAN PETANI DI SULAWESI TENGGARA - Suharno ,; Baharuddin '; Rusdin ' (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Cocoa Farming on Farmers' Income Perspective in Southeast Sulawesi. Southeast Sulawesi cocoafarming became one of the main sources of farmers’income, so the cocoa farmers continued coaching throughvarious approaches. One was conducted by the Institute of Economic Welfare Society (IEWS). This study aims toreveal the cocoa farm performance under the IEWS built, with a focus: (1) Is there a change in the income of cocoafarmers' income after IEWS fostered; (2) What factors are affecting the productivity of cocoa?. Assessment is donethrough a survey of 90 cocoa farmers representing participants and non-participants IEWS spread over ninedistricts the period from March to September 2012. Discussion on the basis of primary data include financingstructures and farm income, enriched with secondary data collected from several agencies relevant related. Thedata were analyzed by descriptive qualitative and quantitative parameters sharpened with finansial profit approachR/C and MBCR to answer the first goal. While to examine the factors that affect the production and income ofcocoa farmers linear regression analysis by incorporating productivity as the dependent variable (Y), and nineindependent variables (X1-X9). The analysis showed: (1) cocoa farming by farmers showed relatively lowperformance, indicated by the use of cocoa clones whose orientation is still of local clones, pest attack andeventually suppress the relatively high productivity of cocoa; (2) Development towards empowering cocoa farmerswho do IEWS proved not give optimal results, it is evident from the analysis that is not real. Performance farmerparticipants IEWS same relative condition with non-participant farmers IEWS; (3) To increase the productivity ofcocoa in the area of assessment, training needs to be focused on the use of superior cocoa clones, and gardenmaintenance to cope with the pest.Keywords: Cocoa farming, productivity, income, IEWSABSTRAKUsahatani kakao di Sulawesi Tenggara menjadi salah satu andalan sumber pendapatan petani, sehinggapembinaan petani kakao terus dilakukan melalui berbagai pendekatan. Salah satunya dilakukan oleh LembagaEkonomi Masyarakat Sejahtera (LEMS). Pengkajian ini bertujuan untuk mengungkap kinerja usahatani kakaoyang berada di bawah binaan LEMS tersebut, dengan fokus: (1) Adakah perubahan pendapatan pendapatan petanikakao setelah dibina LEMS; (2) Faktor-faktor apakah yang mempengaruhi produktivitas kakao? . Pengkajian dilakukan melalui survey terhadap 90 orang petani kakao yang merepresentasikan peserta LEMS dan bukan pesertaLEMS yang tersebar di sembilan kabupaten periode Maret - September 2012. Pembahasan di dasarkan data primermeliputi struktur pembiayaan dan pendapatan usahatani, diperkaya dengan data sekunder yang dikumpulkan daribeberapa instansi terkait yang relevan. Data yang terkumpul dianalisis secara deskriptif kualitatif dan kuantitatifdipertajam dengan parameter keuntungan finalsial menerapkan pendekatan R/C dan MBCR untuk menjawabtujuan pertama. Sementara untuk menguji faktor-faktor yang mempengaruhi produksi dan pendapatan petani kakaodilakukan analisis regresi linear dengan memasukkan produktivitas sebagai peubah tergantung (Y), dan sembilanpeubah bebas (Xi). Hasil analisis menunjukkan: (1) Usahatani kakao oleh petani di lokasi pengkajian menunjukkankeragaan yang relatif rendah, ditunjukkan oleh penggunaan klon kakao yang orientasinya masih banyak klon lokal,serangan OPT relatif tinggi sehingga akhirnya menekan produktivitas kakao; (2) Pembinaan ke arah pemberdayaanpetani kakao yang dilakukan LEMS belum memberikan hasil optimal, terbukti dari analisis yang tidak nyata.Kinerja petani peserta LEMS kondisinya relatif sama dengan petani bukan peserta LEMS; (3) Untuk meningkatkanproduktivitas kakao di wilayah pengkajian, pembinaan perlu difokuskan pada penggunaan klon kakao unggul, danpemeliharaan kebun untuk mengatasi OPT.Kata kunci: Usahatani kakao, produktivitas pendapatan, LEMS